1993
DOI: 10.7326/0003-4819-118-8-199304150-00003
|View full text |Cite|
|
Sign up to set email alerts
|

Acute Mountain Sickness in a General Tourist Population at Moderate Altitudes

Abstract: Acute mountain sickness occurs in 25% of visitors to moderate altitudes and affects activity in most symptomatic visitors. Persons who are younger, less physically fit, live at sea level, have a history of acute mountain sickness, or have underlying lung problems more often develop these symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
264
9
7

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 390 publications
(297 citation statements)
references
References 21 publications
17
264
9
7
Order By: Relevance
“…Increased susceptibility to acute mountain sickness among younger persons was also noted by Hackett and Rennie [2]. Levine et al [3]and Roach et al [4]both noted that the elderly appear to acclimatize well to 2,500 m. These findings are surprising because some physiological components of gas exchange that maintain oxygenation, such as vital capacity and hypoxic ventilatory drive, decrease with age [1, 5, 6]. Levine et al [3]noted that moderate altitude exposure in the elderly is associated with hypoxemia, sympathetic activation, and pulmonary hypertension resulting in a reduced exercise capacity.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Increased susceptibility to acute mountain sickness among younger persons was also noted by Hackett and Rennie [2]. Levine et al [3]and Roach et al [4]both noted that the elderly appear to acclimatize well to 2,500 m. These findings are surprising because some physiological components of gas exchange that maintain oxygenation, such as vital capacity and hypoxic ventilatory drive, decrease with age [1, 5, 6]. Levine et al [3]noted that moderate altitude exposure in the elderly is associated with hypoxemia, sympathetic activation, and pulmonary hypertension resulting in a reduced exercise capacity.…”
Section: Introductionmentioning
confidence: 66%
“…Honigman et al [1]reported that 25% of the visitors from 16 to 87 years of age traveling to moderate elevations developed acute mountain sickness, but this phenomenon occurred mostly in the younger age group. Increased susceptibility to acute mountain sickness among younger persons was also noted by Hackett and Rennie [2].…”
Section: Introductionmentioning
confidence: 99%
“…Hackett et al [10] studied 278 hikers at Pheriche in Nepal, and their results showed that gender did not predispose one to developing AMS. Honigman et al [11] showed that women may be less susceptible to HAPE, but equally as prone to AMS as men. Wang et al [12] also showed no difference in prevalence of AMS between genders.…”
Section: Discussionmentioning
confidence: 99%
“…Maximum altitude gained too influences the likelihood of AHAI-AMS typically develops at altitudes>2,500, HAPO at > 3000 m and HACO between 4000 m -5000 m 18 . A large body of evidence points towards individual susceptibility as an interactive outcome between: genetic and environmental factors 18,19 . Studies on Tibetan and Andean populations have revealed different genetic phenotypes 20 .…”
Section: Epidemiology and Riskmentioning
confidence: 99%